Use of Optical and Electron Microscopy in Evaluating Optimization by Material-Technological Modelling of Manufacturing Processes Involving Cooling of Forgings - Vorel, Ivan; Jeníček, Štěpán; Káňa, Josef; Ibrahim, Khodr; Kotěšovec, Vratislav (Manufacturing Technology Journal, 2016)
From the technological viewpoint, the manufacture of forged parts is a very complex process governed by countless interrelated factors, the most important of which include temperature profiles, and magnitude and velocity of deformation. For a forge shop, a well-established and optimized forging process guarantees sound profit. Given the changing demands of the market, the range of products and the associated manufacturing parameters must be updated frequently and rapidly. In most cases, this means production line stoppages and production capacity losses due to new process development and optimization. Using material-technological modelling, it can be carried out in laboratory conditions instead, without interfering with the production. In this paper, several optimization experiments based on material-technological modelling are evaluated using various optical and electron microscopy methods.
Keywords: Material-technological modelling; cooling optimization; image analysis; scanning electron microscopy